Review on Techniques of Tolerance Design in Mechanical Engineering: A Comprehensive Review and Analysis of Tolerance Design Techniques in Mechanical Engineering (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Tolerance design has become a very sensitive and important issue in product and process development because of increasing demand for a key element in industry for improving product quality and the growing requirements for automation in manufacturing. Tolerance decisions can profoundly impact the quality and cost of product. It is an interactive process between design and manufacturing decision making. Designers want tight tolerances to assure product performance manufacturers prefer loose tolerances to reduce cost. There is a critical need for a quantitative design tool for specifying tolerances. The investigation and comparative analysis of recent studies related to the design requirements in mechanical engineering and manufacturing capabilities together in a common model, where the effects of tolerance specifications on both design and manufacturing requirements can be evaluated quantitatively. In this paper, we presented the systematic review of tolerance design involves repeated computation following two alternate steps (a) tolerance analysis and (b) tolerance synthesis. Significant amount of literature is related to tolerance methods. Summaries of state of the art, the most recent developments, and the outcome of this paper claims the various research gaps identified from literature review.